Analisis Kualitas Layanan Jaringan Internet Berbasis Wireless LAN - Nur Hidaya, Andi Muhammad t; Leniawati, Leniawati (Journal Software, Hardware and Information Technology, 2024)
The development of information and communication technologies has successfully created new technologies that we call Internet technologies. One of the Internet Service Provider (ISP) service providers in Indonesia that is often used is PT. Telkom. Besides, Telkom currently has a product namely Indihome, that offers a package of communications and data services such as home phones, interactive television services and also internet that can be used wirelessly. A wireless-based network application must have a service standard known as Quality Of Service (QoS), where this service aims to analyze the WirelessLan internet network on the indihome service and to find out the quality of the wirelessLAN internet on the Indihome service. This study demonstrates the performance of the network by performing the Action Research (AR) method by measuring the parameters of throughput, package loss and delay using wireshark applications. The results of this study are QoS measurement data on Indihome services based on Tiphon standardization with the average value of the third parameter index of 3.1. Based on the results of the measurement, at network Warkop 27 are in the medium category of the Tiphon Standardization.